Determinan Wirausaha Penyandang Disabilitas di Indonesia: Analisis Kelompok Sektor Primer, Sekunder dan Tersier - Rahimi, Nina; Tan, Firwan; Bachtiar, Nasri (SAFE-Network, 2023)
This research contains an analysis of opportunities for entrepreneurs with disabilities in Indonesia. With a focus on self-employment in three business sector groups (primary, secondary, and tertiary sectors) which aims to answer the question of how the description and determinants of entrepreneurial opportunities for persons with disabilities in Indonesia. This study uses data sourced from the August 2020 National Labor Force Survey (Sakernas) with a total sample of 34,546 respondents with working disabilities consisting of 19,253 respondents in the primary sector, 11,213 respondents in the secondary sector and 4,080 respondents in the tertiary sector. By using the binary logistic regression analysis method, it was found that education, job training, internet access, government policies, and disability classification have a significant effect on the opportunities for entrepreneurs with disabilities in Indonesia in the tertiary sector. In the secondary sector, the entrepreneurial opportunities for persons with disabilities are significantly influenced by work experience, gender, age, location of residence, and disability classification. Meanwhile, in the primary sector, gender, age, internet access, location, and disability classification have a significant effect on the entrepreneurial opportunities of persons with disabilities.